(untitled) (Journal of Nepal Physical Society, 2020)
Human growth hormone (hGH) is synthesized, stored and secreted by somatotropic cells within the lateral wings of the anterior lobe of pituitary glands; and is transported to other organs of human body. Study of intra-molecular structure and its binding mechanisms within the molecule gives more insight of structural stability of the molecule and is also essential in drug designing. In this article, we have investigated the various bonded and non-bonded interactions that contribute for the conformation of entire structure of the hGH molecule using molecular dynamics (MD) simulation. The MD outcomes show that the molecule is hydrophobic in nature. In its conformation, several types of interactions exist, such as disulphide bridges (bonded) and nonbonded: hydrogen bond, hydrophobic, aromatic-aromatic, ionic, aromatic-sulphur, cation-pi.